Taming Balkan nationalism - Okey, Robin (Oxford University Press, 2007)
This is the first full-length history in English of the clash between the Habsburg occupiers of Bosnia-Herzegovina and their Serb, Croat, and Muslim subjects, from 1878 to the fateful assassination of Archduke Franz Ferdinand in 1914.